Oral verrucous carcinoma – a misnomer? Immunohistochemistry based comparative study of two cases - Ray, Jay Gopal (BMJ Publishing Group, 2011)
The clinico-histopathological diagnosis of oral verrucous carcinoma (OVC) is often exclusionary and extremely difficult. Distinction from the classical oral squamous-cell carcinoma (OSCC) is a frequent problem for both clinicians and pathologists because of the extensive nature of the lesion mimicking an invasive cancer. Immunohistochemistry in this case provides a platform for studying distinct molecular mechanism by variation in expression of protein markers. In this study, the authors have attempted to differentiate OVC (case no 1) and OSCC (case no 2) by studying the expression pattern of some well-known tumour marker proteins (vascular endothelial growth factor, matrix metalloproteinases 2 and 9, superoxide dismutase 2 and nicotinamide adenine dinucleotide phosphate quinone oxidoreductase 1). A distinction in expression of these proteins provides a clear understanding that OVC do not show characteristics of a classical carcinoma and may be regarded as a misnomer. This may also provide a better guide for clinicians to differentiate between these two.